Insight and Recommendations for Fragile X-Premutation-Associated Conditions from the Fifth International Conference on FMR1 Premutation - Flora Tassone; Dragana Protic; Emily Graves Allen; Alison D. Archibald; Anna Baud; Ted W. Brown; Dejan B. Budimirovic; Jonathan Cohen; Brett Dufour; Rachel Eiges; Nicola Elvassore; Lidia V. Gabis; et al. (My University, 2023)
The premutation of the fragile X messenger ribonucleoprotein 1 (
Keywords: FMR1; Fragile X Syndrome; Genetics and Neurodevelopmental Disorders